HISTOLOGICAL STRUCTURE OF INTESTINAL TENUE OF THE ETAWAH CROSS BREED GOATS - Cahyadi, I Made Wima; Suwiti, Ni Ketut; Suastika, Putu (Buletin Veteriner Udayana, 2021)
The aim of this research was to determine the histological and morphometry structure of the intestine tenue of Etawah crossbreed. The small intestine samples were taken from sixteen young and adult female and male etawah crossbreed, and then hististological preparations were made with the Harris-Hematoksilin Eosin (HE) method. The results showed the histological structure of the small intestine distinguished from the duodenum, jejunum, and ileum. Composed of four layers: the tunica mucosa is the thickest, submucosa, muscularis, and the thinnest is the tunica serous. The jejunal muscular tunica is thicker than the submucous tunica. Tunica mucosa consists of villi, absorptive cells, goblet cells, paneth cells, lamina propria, intestinal glands, and mucosal muscular lamina. In the tunica muscularis, smooth muscles were arranged in a circle on the inside and elongated outside, while tunica serosa was formed by loose connective tissue. In the tunica submucosa of the duodenum was found the brunner gland, the ileum was found peyer patches, whereas in the jejunum are found loose connective tissue and blood vessels.